The Effectiveness Of Internet Computer Technology In Teaching Vocabulary At The First Year Students Of SMP Negeri 1 Palopo - Suhardi Suhardi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The objective of this research is to find out the effective of ICT in teaching vocabulary, the researcher aimed at finding out the effective of use ICT to the students vocabulary, the population of the research was the first year of SMP Negeri I Palopo, in Academic Year in using the sample, the writer used cluster random sampling, and the total sample is 48 students. This research used pre-experimental method. The instrument of the research was a written test, where consisted of 30 items in three types: multiple choices, matching, and translation. The data analysis of the research showed that the mean score in pretest was 33.35 and in posttest were 83.02. It can be concluded that ICT in teaching vocabulary is effective. The findings of this study were (a) there was effect of English songs in teaching listening, and (b) the effect was, it facilitated and motivated them in learning listening, as shown the result of post-test (67) is higher than the result of pre-test (59.66); and the t-test value (3.2) is greater than t-table value in the level 5% (1.699). Therefore, the null hypothesis is rejected, and alternative hypothesis is accepted